Emotional processes, collective behavior, and social movements: A meta-analytic review of collective effervescence outcomes during collective gatherings and demonstrations - Pizarro, José J.; Zumeta, Larraitz N.; Bouchat, Pierre; Włodarczyk, Anna; Rimé, Bernard; Basabe, Nekane; Amutio, Alberto; Páez, Darío (Frontiers in Psychology, 2022)
In this article, we review the conceptions of Collective Effervescence (CE) –a state of intense shared emotional activation and sense of unison that emerges during instances of collective behavior, like demonstrations, rituals, ceremonies, celebrations, and others– and empirical approaches oriented at measuring it. The first section starts examining Émile Durkheim's classical conception on CE, and then, the integrative one proposed by the sociologist Randall Collins, leading to a multi-faceted experience of synchronization (e.g., Páez and colleagues, 2015). Then, we analyze the construct as a process emerging in collective encounters when individuals contact with social ideal and values, referring to the classical work of Serge Moscovici as well as those more recent empirical approaches (e.g., Shira Grabriel and colleagues, 2017). Third, we consider CE as a set of intense positive emotions linked to processes of group identification, as proposed by authors of the Social Identity Theory tradition (e.g., Nick Hopkins and colleagues, 2016). Finally, we describe CE from the perspective of self-transcendence (e.g., emotions, experiences; Scott Draper, 2014), and propose a unified description of this construct. The second section shows the results of a meta-analytical integration (k = 50, N = 182738) aimed at analyzing CE’s proximal effects or construct validity (i.e., Individual Emotions and Communal Sharing) as well as its association with more distal variables, such as Collective Emotions, Social Integration, Social Values and Beliefs and Empowerment. Results indicate that CE strongly associates with Individual Emotions –in particular, Self-Transcendent Emotions– and Communal Sharing constructs (e.g., Group Identity, Fusion of Identity), providing construct validity. Among the distal effects of CE, it is associated with Collective Positive Emotions, long-term Social Integration (e.g., Ingroup Commitment), Social Values and Beliefs and Empowerment-related variables (e.g., Well-Being, Collective Efficacy, Collective Self-Esteem). Among the moderation analyses carried out (e.g., study design, CE scale, type of collective gathering), the effects of CE in demonstrations are noticeable, where this variable is a factor that favors other variables that make collective action possible, such as Group Identity (rpooled = .52), Collective Efficacy (rpooled = .37), Negative and Self-Transcendent Emotions (rpooled = .14 and .58), and Morality-related beliefs (rpooled = .43).